KEBUTUHAN ARMADA OPTIMAL BUS RAPID TRANSIT (BRT) TRANS SEMARANG KORIDOR II (TERMINAL TERBOYO – TERMINAL SISEMUT) - Irin Aerina Wahyu Ramadhan; Reny Yesiana (Jurnal Riptek, 2018)
Semarang city as the capital of Central Java Province has a population about 1.729.428 people in 2016 (BPS Semarang, 2017). The population is increasing and the rate of urbanization has impact on the rapid increase in the number of private vehichles and pose a problem like a traffic jam. Bus Rapid Transit (BRT) Trans Semarang is Semarang City government strategy to reduce a traffic jam. Based on data of Trans Semarang passengers, corridor II was the highest number of passengers among other corridors that use medium-sized buses and there is a queue of passengers at transit stop.The study aims to analysis buses optimal required by corridor II to avoid possible over supply. The number of optimal calculated by consider on income operator based on cost namely by counting factors load (load factor) as well as consider operational costs a vehicle (BOK). The method of analysis that used be the method of qualitative and quantitative. Qualitative analysis method used to described a data shaped writing while quantitative to described data numbers or nominal. Data cost for vehicle’s operational obtained from BLU Trans Semarang, then load factor data obtained from the load factor dynamic survey in weekday and weekand at the rush hour on morning and afternoon. Number of optimal can be counted through existing load factor in the break even and number of existing. The survey and data analysis shows corridor II with the total number of 24 unit ready operation have not reached balance. The analysis of the optimal vehicle show that the corridor II requires 26 units of vehicles.